Gender composition at work and women's career satisfaction: An international study of 35 societies - Jane L. Y. Terpstra-Tong; Len J. Trevi\~no; Alara Cansu Yaman; Fabian Jintae Froese; David A. Ralston; Nikos Bozionelos; Olivier Furrer; Brian Tjemkes; Fidel León-Darder; Yongjuan Li; Pingping Fu; Mario Molteni; et al. (Human Resource Management Journal, 2024)
Drawing from status characteristics theory, we develop a multilevel model to explain the relationships between gender composition (e.g., female-female supervisor-subordinate dyads, a female majority at the next higher level, and a female majority at the same job level) in the workplace and women's career satisfaction. We hypothesise that working with a female supervisor and a female majority at the same level will be negatively related to women's career satisfaction, while a female majority at the next higher level will be positively related to women's career satisfaction. Moreover, we propose that formal societal (gender-equality) institutions and informal cultural (gender-egalitarian) values, each has a moderating effect on the impact of gender compositions on women's career satisfaction. Our results from a multilevel analysis of 2291 women across 35 societies support the three hypothesised main effects. Whereas institutions that support gender equality weaken the positive effect of working with a female majority at the next higher level, they amplify the negative effect of a female majority at the same hierarchical level. Our findings highlight the complex and paradoxical nature of gender composition effects on women's career satisfaction. We discuss the theoretical contributions of our findings and their implications for the diversity management practices of multinational enterprises.
Keywords: 650; career satisfaction; gender status beliefs; intragender competition/cooperation; paradox; queen bee phenomenon; status characteristics theory